Teaching Methods and Quality of Business Studies Textbook in Secondary Schools in Kenya - Sarah Getahun Bekele; Paul Odundo Amollo; John Kamau Mwangi; Ganira Khavugwi Lilian (Journal La Edusci, 2021)
Well-structured business studies textbook provides enjoyable episodes of knowledge creation which promotes achievement learning outcome for sustained academic results. Business textbook represents potentially implemented curriculum as its vehicle through which intended curriculum is availed to learner encouraging achievement of learning objectives. However, adopting methodology that does not facilitate achievement of specific objectives may limit knowledge construction degrading learner’s mean score. The study adopted is exploratory research design. Data collected were both quantitative and qualitative. Quantitative data were analyzed through counts, percentages, means, standard deviations and Chi square tests while Qualitative data were analyzed using content analysis. Cross tabulation results further indicated that teaching methods significantly influence quality of textbook implying that appropriate teaching methods supports achievement of learning. It was also found that presentation, visuals and differentiated instruction influence quality of instruction content encouraging learning. Therefore, it is recommended that teaching method selected should be learner centered to accelerate learning.